Tilted Implants: An Alternative to Conventional Fabricated Dentures - Vijay Ebenezer1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Rehabilitation of patients with completely edentulous maxilla and mandible with implant becomes difficultbecause of less bone quantity, poor bone quality, maxillary sinus in posterior maxilla and mental foramen andmandibular canal in mandible. Sinus lifting procedure and bone augmentation procedure were required totreat such patients, prior to implant placement. This article reviews on an alternative treatment procedure inwhich two posterior implants are placed at an angle eliminating the need for sinus lift or bone augmentationprocedures.